Health-Relevant Leadership Behaviour: A Comparison of Leadership Constructs. (February 2014) - Gregersen, Sabine; Vincent-Höper, Sylvie; Nienhaus, Albert
There is empirical evidence that leadership behaviour is related to employee well-being. Most studies have analysed the relation between individual leadership constructs and indicators of employee well-being. There has been no systematic comparison of different leadership constructs with respect to their impact on different indicators of employee well-being within the same sample. The aim of our study was therefore to compare different leadership constructs with respect to their relation with indicators of positive and negative employee well-being. The sample consists of 1, 045 health care workers. We conducted relative weight analyses and hierarchical regression analyses in order to identify the best leadership predictor for employee well-being. Our analyses reveal that leader-member exchange best predicts most of the well-being indicators and that the other leadership constructs fail to add substantial additional variance. Our findings advance the understanding of how leaders can enhance employee well-being and provide implications for research and practice.